The Effect of Regional Original Income, Balanced Funds and Capital Expenditures on Financial Performance of Regency/City Governments in the Special Region of Yogyakarta in 2010-2019 - Sriwinarti, Asih; Artaningtyas, Wahyu Dwi (RSF Conference Series: Business, Management and Social Sciences, 2021)
The financial enforcement of local governments is one dimension that can guarantee regions’ ability to explore and manage local financial sources to support the government system and regional development without moving utterly reliant on the central government. One of the regional financial performance measurement tools is the regional independence ratio. Regencies/Cities in DIY are regions whose financial performance is still relatively different. Therefore it needs to investigate the factors that are the matter. The purpose of this study was to analyze the effect of Regional Original Income, Balanced funds, and Capital Expenditures on the financial performance of Regency/City Governments in the Special Region of Yogyakarta. The data adopted in this research is panel data, a combination of data for time-series 2010-2019, and a cross-section of five regencies/cities in DIY. The result of panel data regression analysis shows that the Regional Original Income and Capital Expenditure have a positive and significant effect. In contrast, the Balanced fund has a negative and significant effect on the financial performance of the regency government in DIY.